Investing across Borders with Heterogeneous Firms : Do FDI-Specific Regulations Matter? - Wagle, Swarnim (2012)
This paper revisits the institutional determinants of foreign direct investment (FDI) using a comprehensive new data set on the regulations that govern FDI in more than 80 countries. It exploits the presence of confirmed zero investment flows between countries to estimate productivity cut-offs of firms that invest abroad profitably. This approach corrects likely biases arising from firm heterogeneity and country selection in a theoretically derived gravity-type model. The analysis finds inward FDI to be highly responsive to cross-country variation in specific institutional provisions, such as arbitration of disputes and legal procedures to establish foreign subsidiaries. The importance of FDI-specific provisions stands out even after controlling for the general quality of institutions. Statutory openness to FDI, however, has no association with actual inflow of investment. These results are found to be robust to different specifications.